The PUCP Case and Will Interpretation - Atienza, Manuel (2010)
The material patrimony of the Pontifical Catholic University of Peru is a complex issue since it is questioned how these will be managed and above all who will be the managers. The records indicate that several wills were issued, but there are two relevant wills. The first of these two was in 1933 and the second one in 1938. Recently, the PUCP requested a writ of amparo proceeding due to the violation of their constitutional rights as the right of property and the right of university autonomy. Thus, on March 17, 2010, the Constitutional Court declared the legal protection process unfounded in a judgment that deserves attention given its legal argumentative content. Based on this, the professor Manuel Atienza performs a cross-sectional analysis of the decision of each of the magistrates who issued the judgment. Consequently, this work evaluates the legal argumentation of the sentence handed down by the majority of the judges of the Constitutional Court. First, this article criticizes the competence exercised by the Constitutional Court regarding substantive issues that it could not develop. Second, this article criticizes the handling and use of language used by the TC in which it becomes a partial language. Third, it will analyze the legal foundations that the magistrates used. Especially, it presents a special emphasis on the doctrine about the interpretation of the wills which the TC used in its argumentation. The author presents his thesis in which the application of the proportionality trial in the present case stands out.